A Prospective Controlled Study on Long-Term Outcomes of Facial Lacerations in Children - Fontana, Sonja; Schiestl, Clemens M.; Landolt, Markus A.; Staubli, Georg; von Salis, Sara; Neuhaus, Kathrin; Mohr, Christoph; Elrod, Julia (Frontiers in Pediatrics, 2021)
Background: Although skin adhesives have been used for decades to treat skin lacerations, uncertainty remains about long-term results and complications. Methods: In this prospective, controlled, single-blinded study, outcomes were assessed by five plastic surgeons with standardized photographs at 6-12 months using a modified Patient and Observer Scar Assessment Scale (POSAS) and Vancouver Scar Scale (VSS); additionally, the POSAS was performed by the patients/caregiver(s) and the physician; pain, requirement of anesthesia, treatment time, costs, complications and Quality of live (Qol) were assessed. Results: 367 patients were enrolled; 230 were included in the main analysis. 96 wounds were closed using tissue adhesives (group 1); 134 were sutured (group 2). Assessment by the independent observers revealed an improved mean modified overall POSAS-score in group 1 in comparison to group 2 (2.1, 95% CI [1.97-2.25] vs 2.5, 95% CI [2.39-2.63]; p< 0.001, d = 0.58) and mean VSS-score (1.2, 95% CI [0.981-1.34] vs 1.6, 95% CI [1.49-1.79], p< 0.001, d = 0.53). At the early follow-up, dehiscence rate was 12.5% in group 1 and 3.7% in group 2 (p< 0.001), later on 1 dehiscence remained per group. Mild impairment of QoL was found at the early follow-up in both groups, with no impairment remaining later on. Duration of treatment and treatment costs were lower in group 1. Conclusion: Both modalities of wound closure yield favorable aesthetic results and complications are rare. Adhesives are more cost-effective and application is less time-consuming, therefore, tissue adhesives offer considerable advantages when used appropriately.